A Secure Gateway Localization and Communication System for Vehicular Ad Hoc Networks - Wang, Yan (Université d'Ottawa / University of Ottawa, 2013)
Intelligent Transport System (ITS) has become a hot research topic over the past decades. ITS is a system that applies the following technologies to the whole transportation management system efficiently, including information technique, wireless communication, sensor networks, control technique, and computer engineering. ITS provides an accurate, real time and synthetically efficient transportation management system. Obviously, Vehicular Ad Hoc NETworks (VANETs) attract growing attention from both the research community and industry all over the world. This is because a large amount of applications are enabled by VANETs, such as safety related applications, traffic management, commercial applications and general applications. When connecting to the internet or communicating with different networks in order to access a variety of services using VANETs, drivers and passengers in different cars need to be able to exchange messages with gateways from their vehicles. A secure gateway discovery process is therefore critical, because vehicles should not be subject to security attacks while they are communicating; however, currently there is no existing protocol focusing on secure gateway discovery. In this thesis, we first analyze and compare current existing secure service discovery protocols and then we propose a Secure Gateway Localization and Communication System for Vehicular Ad Hoc Networks (SEGAL), which concentrates on the security issue in gateway discovery. We focus on the authentication aspect by proposing secure cluster based VANETs, that can ensure the gateway discovery messages exchanged through secure clusters. We present the principle and specific process of our SEGAL protocol and analyze its performance to guarantee its outstanding practical applicability.
Keywords: VANETs; Secure Gateway Discovery Protocol; Cluster-based Protocol; network security